2016
DOI: 10.3389/fncom.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Self-Sustained Oscillatory States in Hierarchical Modular Networks with Mixtures of Electrophysiological Cell Types

Abstract: In a network with a mixture of different electrophysiological types of neurons linked by excitatory and inhibitory connections, temporal evolution leads through repeated epochs of intensive global activity separated by intervals with low activity level. This behavior mimics “up” and “down” states, experimentally observed in cortical tissues in absence of external stimuli. We interpret global dynamical features in terms of individual dynamics of the neurons. In particular, we observe that the crucial role both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 52 publications
7
42
0
6
Order By: Relevance
“…We have shown elsewhere the importance of this disinhibitory effect to sustain the long-lived activity of the network in the oscillatory situation (Tomov et al, 2016).…”
Section: Preliminaries and The Deterministic Setupmentioning
confidence: 85%
See 4 more Smart Citations
“…We have shown elsewhere the importance of this disinhibitory effect to sustain the long-lived activity of the network in the oscillatory situation (Tomov et al, 2016).…”
Section: Preliminaries and The Deterministic Setupmentioning
confidence: 85%
“…In the distribution shown in Fig 5.2 G, the maximum is broad due to the time-scale separation of the variables: u is slower than v and its relaxation takes much longer. In (Tomov et al, 2016) we have shown the importance of the recovery variable for the breakdown of global high-activity epochs, which produces the up and down oscillatory pattern. The term "up" refers here to different states in which the network activity is above Figure 5.2: Up and down network oscillations in the noiseless case when g in > g ex .…”
Section: Preliminaries and The Deterministic Setupmentioning
confidence: 88%
See 3 more Smart Citations